2000
DOI: 10.1002/jor.1100180523
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of hyaluronic acid and phospholipid prevents adhesion formation on the injured flexor tendon in rabbits

Abstract: Dipalmitoyl phosphatidylcholine, a highly surface-active polar lipid, has been implicated as a potential boundary lubricant for synovial joints. We examined the effects of dipalmitoyl phosphatidylcholine on the flexor tendon and its protective effect against postoperative adhesion in two experimental steps. First, the flexor digitorum fibularis and the distal pulley of rabbits were set for a friction test. The test was performed with saline solution, sodium hyaluronate, or a mixture of dipalmitoyl phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 24 publications
0
31
0
2
Order By: Relevance
“…Second, we did not test either the cell-based therapy or surface modification alone. However, some studies have shown that bone marrow stromal cells do increase tendon healing capacity [8,10,15], and others have shown that surface modification decreases tendon adhesions [14,40]. Therefore, the purposes of our study were to investigate the effects of combining these treatments on postoperative adhesion formation and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not test either the cell-based therapy or surface modification alone. However, some studies have shown that bone marrow stromal cells do increase tendon healing capacity [8,10,15], and others have shown that surface modification decreases tendon adhesions [14,40]. Therefore, the purposes of our study were to investigate the effects of combining these treatments on postoperative adhesion formation and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we found that surface modification with carbodiimide-derivatized HA combined with lubricin (cd-HA-lubricin) greatly reduced tendon adhesion and improved digital function but also adversely affected tendon healing 20,21 . In addition to HA and lubricin, phospholipids also have been found to decrease tendon gliding resistance and improve outcomes after flexor tendon repair 22 . All three lubricating molecules are native components of synovial fluid and are found on the intrasynovial tendon surface [23][24][25] .…”
mentioning
confidence: 99%
“…The polysaccharide hyaluronic acid (HA) is the main component of the joint fluid. It is produced by the synovial membrane and forms a high molecular mass complex [16,17]. Both aging and arthritis can reduce both the concentration and the relative molecular weight of HA, and thus reduce the viscosity of the synovial fluid.…”
Section: Abrasive Wearmentioning
confidence: 99%
“…The work (force × distance) becomes an important parameter for estimating the adhesion formation on the injured flexor tendon that cannot withstand the reciprocating motions of a pendulum test [17].…”
Section: Tribological Testing Of Tissue From a Living Bodymentioning
confidence: 99%